Millennial capitalism and the culture of neoliberalism - Comaroff, John L., 1945- (Millennial quartet., 2001)
A special issue of PUBLIC CULTURE, this collection of essays forms an empirically grounded, conceptual discussion that posits global millennial capitalism as a historical formation.